Electrode plate and preparation method and application thereof

By adding aryl lithium material as a solid filler to the active material layer of the solid-state battery electrode sheet, the problems of high porosity and large interface impedance of the electrode sheet are solved, and the electrochemical performance is improved.

CN119833540APending Publication Date: 2025-04-15CHONGQING FUDI BATTERY RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311832222.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-27
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the prior art, the electrode sheet porosity of the solid-state battery has a high porosity, resulting in an increase in interface impedance, and a small contact area between the active material and the solid-state electrolyte, which affects the electrochemical performance. At the same time, the applied pressure rolling process will damage the shape and mechanical properties of the electrode sheet.

Method used

By adding a solid filler, especially an aryl lithium material, to the active material layer of the electrode sheet, the porosity of the electrode sheet is reduced, the contact area of ​​each component of the active material layer is increased, the interface impedance is reduced, and the conductivity of ions and electrons is improved.

Benefits of technology

The low porosity and low interface impedance of the electrode sheet are achieved, and the electrochemical performance of solid-state batteries is improved, including ionic conductivity and electronic conductivity, and the overall performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833540A_ABST
    Figure CN119833540A_ABST
Patent Text Reader

Abstract

The invention provides an electrode plate and a preparation method and application thereof, the electrode plate comprises a current collector and an active material layer arranged on the surface of the current collector, the active material layer comprises an active material, a binder and a solid filler, and the solid filler comprises an aryl lithium material. The electrode plate is low in porosity, low in interface impedance and excellent in ionic conductivity and electronic conductivity, and the electrochemical performance of the electrode plate can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to an electrode sheet and a preparation method and application thereof. Background Art

[0002] At present, in solid-state batteries, it is necessary to reduce the porosity of the electrode sheet and increase the contact area between the active material in the electrode sheet and the solid electrolyte, so as to reduce the interface impedance and improve the conductivity of the electrode sheet. In the related art, the electrode sheet is mainly rolled by applying external pressure to reduce the porosity of the electrode sheet, but the active material and the solid electrolyte still maintain point-to-point contact, and the problem of increased interface impedance still exists. At the same time, the shape and mechanical properties of the electrode sheet will be damaged during the application of external pressure. Therefore, it is necessary to provide an electrode sheet with low porosity without external pressure, so as to reduce the interface impedance of the solid-state battery and improve the electrochemical performance of the electrode sheet. Summary of the invention

[0003] In view of this, the present application provides an electrode sheet and a preparation method and application thereof. The electrode sheet has low porosity, low interface impedance, and excellent ionic conductivity and electronic conductivity. Using it in solid-state batteries can improve the electrochemical performance of solid-state batteries, which is conducive to the widespread application of solid-state batteries.

[0004] In a first aspect, the present application provides an electrode sheet, comprising a current collector and an active material layer disposed on a surface of the current collector, wherein the active material layer comprises an active material, a binder and a solid filler, and the solid filler comprises an aryl lithium material.

[0005] In the embodiment of the present application, the porosity of the electrode sheet is less than or equal to 18%.

[0006] In the embodiment of the present application, the mass percentage of the solid filler in the electrode sheet is 0.1%-1%.

[0007] In an embodiment of the present application, the aryl lithium material includes at least one of naphthalene lithium, biphenyl lithium, anthracene lithium and derivatives thereof.

[0008] In an embodiment of the present application, the Young's modulus of the aryl lithium material is 18 GPa-30 GPa.

[0009] In an embodiment of the present application, the particle size of the active material is 0.5μm-15μm; the active material includes a positive electrode active material and a negative electrode active material; the positive electrode active material includes at least one of lithium cobalt oxide material, lithium manganese oxide material, nickel cobalt manganese material and nickel cobalt aluminum material; the negative electrode active material includes at least one of graphite, acetylene black, graphene, activated carbon, metallic lithium, lithium-indium alloy, silicon and lithium titanate.

[0010] In an embodiment of the present application, the active material layer further includes a conductive agent, and the mass ratio of the active material, the conductive agent and the binder is (60-99.9):(1-20):(0.1-20).

[0011] In an embodiment of the present application, the conductive agent includes at least one of graphite, carbon black, acetylene black and graphene; the binder includes at least one of polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, polystyrene, polybutadiene, acrylic resin, epoxy resin, polyethylene oxide, sodium carboxymethyl cellulose and styrene-butadiene latex.

[0012] In the embodiment of the present application, the active material layer also includes an electrolyte, and the electrolyte includes LSPO (Li 3.5 Si 0.5 P 0.5 O4) type solid electrolyte, lithium-rich antiperovskite solid electrolyte, halogen solid electrolyte, sulfur solid electrolyte or more.

[0013] In an embodiment of the present application, the particle size of the electrolyte is 1 μm-5 μm, and the mass ratio of the active material to the electrolyte is (60-99.9):(5-50).

[0014] In the electrode sheet provided in the present application, the solid filler reduces the porosity of the electrode sheet, increases the contact area of ​​each component in the active material layer, reduces the interface impedance between grains, improves the ionic conductivity and electronic conductivity, and thus improves the electrochemical performance of the solid-state battery.

[0015] In a second aspect, the present application provides a method for preparing an electrode sheet, comprising:

[0016] The active material and the binder are mixed to obtain a mixed slurry, and the mixed slurry is coated on the surface of the current collector to obtain a prefabricated electrode sheet;

[0017] The prefabricated electrode sheet is immersed in a solid filler solution, and after the immersion is completed, the electrode sheet is dried to obtain the electrode sheet; the solid filler in the solid filler solution includes an aryl lithium material.

[0018] In the examples of the present application, the concentration of the solid filler solution is 0.8 mol / L-1.2 mol / L; and the immersion time is 5 min-20 min.

[0019] The electrode sheet preparation method provided in the present application is novel, the preparation process is simple, and the prepared product has excellent performance.

[0020] In a third aspect, the present application provides a solid-state battery, comprising a positive electrode sheet and a negative electrode sheet, and a solid electrolyte layer arranged between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet and / or the negative electrode sheet comprises the electrode sheet described in the first aspect or the electrode sheet prepared by the preparation method described in the second aspect.

[0021] In an embodiment of the present application, the positive electrode plate includes a positive electrode collector and a positive electrode active material layer arranged on the surface of the positive electrode collector, and the negative electrode plate includes a negative electrode collector and a negative electrode active material layer arranged on the surface of the negative electrode collector; the thickness ratio of the positive electrode active material layer, the negative electrode active material layer and the solid electrolyte layer is (20-50):(10-30):(20-40).

[0022] The solid-state battery provided in this application has low interface impedance, good conductivity and excellent electrochemical performance.

[0023] In a fourth aspect, the present application provides an electrical device, wherein the electrical device comprises the solid-state battery described in the third aspect.

[0024] The electrical equipment provided in this application has excellent comprehensive performance, greatly improved safety performance, and strong product competitiveness. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the embodiments or the prior art description. The specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0026] Figure 1 A flow chart of a method for preparing an electrode sheet provided in one embodiment of the present application;

[0027] Figure 2 A cross-sectional schematic diagram of a solid-state battery provided in accordance with one embodiment of the present application. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0029] In the related art, there are a large number of pores in the electrode sheet, and the components in the active material layer are in point-to-point contact, with a small contact area, a large inter-grain interface impedance, and poor conductivity of the electrode sheet. By applying external pressure to the electrode sheet for rolling, the porosity in the electrode sheet can be reduced, but the contact area between the components in the active material layer cannot be changed, and thus the interface impedance cannot be improved. In addition, the rolling operation of the electrode sheet with external pressure will cause the electrode sheet to wrinkle and stretch, reducing its mechanical properties.

[0030] In order to solve the above technical problems, the present application provides an electrode sheet, which reduces the porosity of the electrode sheet by adding a solid filler to fill the pores in the active material layer, increases the contact area between the components in the active material layer, and reduces the interface impedance between the grains. At the same time, the solid filler includes an aryl lithium material, which is an ion / electronic mixed conductive material, which can improve the ionic conductivity and electronic conductivity of the electrode sheet, which is beneficial to improving the comprehensive electrochemical performance of the electrode sheet.

[0031] In the present application, the electrode sheet includes a current collector and an active material layer arranged on the surface of the current collector, the active material layer includes an active material, a binder and a solid filler, and the solid filler includes an aryl lithium material. The current collector has the function of conducting electrons and carrying the active material layer, and the active material layer is an important component of the electrode sheet, including active materials, binders and solid fillers, wherein the active material is a key substance that determines the performance of the battery, the binder can improve the binding ability of each component in the active material layer, improve the bonding ability between the active material layer and the current collector, and the solid filler can fill the pores in the electrode sheet to reduce the porosity of the electrode sheet, increase the contact area between the active materials, and reduce the interface impedance between the grains. In addition, the aryl lithium material is an ion / electronic mixed conductive material, which increases the number of electronic and ion conductive pathways, and can improve the ionic conductivity and electronic conductivity of the electrode sheet. The porosity of the electrode sheet is small, the contact area between the active material and the electrolyte is increased, the ionic conductivity and electronic conductivity pathways are increased, and the comprehensive electrochemical performance is improved, which is conducive to the wide application of electrode sheets and solid-state batteries.

[0032] In one embodiment of the present application, the solid filler includes an aryl lithium material. After certain groups on the aromatic ring in the aromatic hydrocarbon are lithiated, a flexible aryl lithium is obtained, which can expand the contact area between the active materials and reduce the interface impedance. At the same time, the aryl lithium is an ion / electron mixed conductive material, which can improve the ionic conductivity and electronic conductivity in the electrode sheet. Specifically, the solid filler can be, but is not limited to, one or more of naphthalene lithium, biphenyl lithium, anthracene lithium and their derivatives. In one embodiment of the present application, the solid filler can be naphthalene lithium. In another embodiment of the present application, the solid filler can be biphenyl lithium.

[0033] In one embodiment of the present application, the Young's modulus of the aryl lithium material is 18GPa-30Gpa. The aryl lithium material is a layered crystal structure obtained by compounding aryl groups and lithium ions. The bonding force between the layers in the aryl lithium material is small, easy to slide and spread, and the layers are prone to breakage. Therefore, the smaller the Young's modulus of the aryl lithium, the better the flexibility, which is conducive to the filling of the electrode sheet and reduces the porosity of the electrode sheet. Specifically, the Young's modulus of the aryl lithium material can be, but is not limited to, 18GPa, 20GPa, 22GPa, 25GPa, 28GPa or 30GPa, etc. In one embodiment of the present application, the Young's modulus of the aryl lithium material can be 18GPa-26Gpa. In another embodiment of the present application, the Young's modulus of the aryl lithium material can be 22GPa-30Gpa. In some embodiments, the Young's modulus test method of the aryl lithium material can be, but is not limited to, one of the static tensile method, the bending method, and the dynamic resonance method.

[0034] In one embodiment of the present application, the mass percentage of the solid filler in the electrode sheet is 0.1%-1%. The appropriate amount of solid filler can give full play to its filling effect, so that the solid particles in the active material layer can be fully bridged, and the density of the electrode sheet can be improved. At the same time, the utilization rate of the solid filler can be increased, the interface impedance can be reduced, and the energy density of the electrode sheet can be increased. Specifically, the mass percentage of the solid filler in the electrode sheet can be, but not limited to, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc. In one embodiment of the present application, the mass percentage of the solid filler in the electrode can be 0.1%-0.5%. In another embodiment of the present application, the percentage of the solid filler in the electrode sheet can be 0.4%-1%.

[0035] In one embodiment of the present application, the active material may be a positive electrode active material or a negative electrode active material. The active material acts as an energy storage material during the charge and discharge process, and determines the comprehensive performance of the electrode sheet. In some embodiments, the active material includes a positive electrode active material, in which case the electrode sheet is a positive electrode sheet, the electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the surface of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material, a binder, and a solid filler. In some embodiments, the active material includes a negative electrode active material, in which case the electrode sheet is a negative electrode sheet, the electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material, a binder, and a solid filler. Specifically, the positive electrode active material may be, but is not limited to, one or more of a lithium cobalt oxide material, a lithium manganese oxide material, a nickel cobalt manganese material, and a nickel cobalt aluminum material, and the negative electrode active material may be, but is not limited to, one or more of graphite, acetylene black, graphene, activated carbon, metallic lithium, lithium-indium alloy, silicon, and lithium titanate. In one embodiment of the present application, the positive electrode active material may be a lithium cobalt oxide material, and the negative electrode active material may be a graphite material. In another embodiment of the present application, the positive electrode active material may be a lithium manganese oxide material, and the negative electrode active material may be a silicon material.

[0036] In one embodiment of the present application, the particle size of the active material is 0.5μm-15μm. The appropriate particle size of the active material can increase the contact area between the active materials and improve the conductivity and density of the electrode sheet. Specifically, the particle size of the active material can be, but is not limited to, 0.5μm, 1μm, 3μm, 4μm, 5μm, 7μm, 8μm, 10μm, 12μm, 14μm, 15μm, etc. In one embodiment of the present application, the particle size of the active material can be 0.5μm-7μm. In another embodiment of the present application, the particle size of the active material can be 5μm-15μm.

[0037] In one embodiment of the present application, the binder can improve the binding ability of each component in the active material layer and improve the binding ability between the active material layer and the current collector. Specifically, the binder can be, but is not limited to, one or more of polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, polystyrene, polybutadiene, acrylic resin, epoxy resin, polyethylene oxide, sodium carboxymethyl cellulose and styrene-butadiene latex. In one embodiment of the present application, the binder can be polyvinylidene fluoride. In another embodiment of the present application, the binder can be sodium carboxymethyl cellulose.

[0038] In one embodiment of the present application, the mass ratio of the active material to the binder is (60-99.9): (0.1-20). Specifically, the mass ratio of the active material to the binder may be, but is not limited to, 60: 1, 60: 10, 60: 15, 70: 5, 75: 10, 80: 5, 90: 3, 99.9: 20, etc. In one embodiment of the present application, the mass ratio of the active material to the binder may be (75-85): (1-3), which may further improve the bonding ability and conductivity of the electrode sheet. In another embodiment of the present application, the mass ratio of the active material to the binder may be (60-95): (1-5). In yet another embodiment of the present application, the mass ratio of the active material to the binder may be (90-99.9): (0.1-10).

[0039] In one embodiment of the present application, the active material layer also includes a conductive agent, which can increase the conductivity between the active materials and improve the electronic conductivity. Specifically, the conductive agent can be, but is not limited to, one or more of graphite, carbon black, acetylene black and graphene. In one embodiment of the present application, the conductive agent can be graphite. In another embodiment of the present application, the conductive agent can be carbon black.

[0040] In one embodiment of the present application, the mass ratio of the active material, the conductive agent and the binder is (60-99.9): (1-20): (0.1-20). Specifically, the mass ratio of the active material, the conductive agent and the binder may be, but is not limited to, 60:1:0.1, 60:1:1, 70:1:3, 75:5:4, 80:5:6, 60:4:7, 80:10:1, 90:15:10, 95:3:5, 99.9:20:20, etc. In one embodiment of the present application, the mass ratio of the active material, the conductive agent and the binder may be (75-85): (1-3): (1-5). In another embodiment of the present application, the mass ratio of the active material, the conductive agent and the binder may be (60-95): (1-10): (1-10).

[0041] In one embodiment of the present application, the current collector plays the role of conducting electricity and carrying the active material layer, including a positive current collector or a negative current collector. In some embodiments, the current collector includes a positive current collector, in which case the electrode sheet is a positive electrode sheet, the electrode sheet includes a positive current collector and a positive electrode active material layer disposed on the surface of the positive current collector, and the positive electrode active material layer includes a positive electrode active material, a binder, a conductive agent, and a solid filler. In some embodiments, the current collector includes a negative current collector, in which case the electrode sheet is a negative electrode sheet, the electrode sheet includes a negative current collector and a negative electrode active material layer disposed on the surface of the negative current collector, and the negative electrode active material layer includes a negative electrode active material, a binder, and a solid filler. Specifically, the current collector may be, but is not limited to, one or more of copper, aluminum, nickel, and stainless steel. In one embodiment of the present application, the positive current collector may be aluminum foil, and the negative current collector may be copper foil.

[0042] In one embodiment of the present application, the active material layer also includes an electrolyte. For some active materials with poor ion conductivity, an electrolyte needs to be added to the active material layer to improve the ion conductivity between the active material layers and between the active material layer and the solid electrolyte layer. Specifically, the electrolyte can be but is not limited to LSPO (Li 3.5 Si 0.5 P 0.5 O4) type solid electrolyte, lithium-rich antiperovskite type solid electrolyte, halogen solid electrolyte, sulfur solid electrolyte one or more. In one embodiment of the present application, the electrolyte can be a sulfur solid electrolyte, which is beneficial to improve the ionic conductivity of the electrode sheet.

[0043] In one embodiment of the present application, the sulfur-based solid electrolyte includes a sulfur-based crystalline electrolyte and a sulfur-based glassy electrolyte, which has a higher ionic conductivity. Specifically, the sulfur-based solid electrolyte can be, but is not limited to, Li 6-x PS 5-x Cl 1+x , Li 11-y M 2-y P 1+y S 12 , 75Li2S·25P2S5, wherein 0≤x≤0.8, M is Ge or Si, and 0.5≤y≤1.5. Exemplary sulfur-based solid electrolytes may be, but are not limited to, Li 5.6 PS 4.6 Cl 1.4 , Li 5.8 PS 4.8 Cl 1.2 , Li 10 GeP2S 12 , Li 10.5 Si 1.5 P 1.5 S 12 In one embodiment of the present application, when the positive electrode active material is a lithium cobalt oxide material, the electrolyte in the positive electrode active material layer may be Li 5.6 PS 4.6 Cl 1.4 In another embodiment of the present application, when the positive electrode active material is a lithium manganate material, the electrolyte in the positive electrode active material layer may be Li 10.5 Si 1.5 P 1.5 S 12 In another embodiment of the present application, when the negative electrode active material is a silicon material, the electrolyte in the negative electrode active material layer may be Li 5.8 PS 4.8 Cl 1.2 .

[0044] In one embodiment of the present application, the particle size of the electrolyte is 1μm-5μm, and the electrolyte can be filled between the active materials. The appropriate particle size can increase the contact area between the electrolyte and the active material and improve the conductivity of the active material layer. Specifically, the particle size of the electrolyte can be, but is not limited to, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, etc. In one embodiment of the present application, the particle size of the electrolyte can be 1μm-3.5μm. In another embodiment of the present application, the particle size of the electrolyte can be 2μm-5μm.

[0045] In one embodiment of the present application, the mass ratio of active material, electrolyte, conductive agent and binder is (60-99.9): (5-50): (1-20): (0.1-20). Specifically, the mass ratio of active material, electrolyte, conductive agent and binder can be, but is not limited to, 60:5:1:0.1, 60:5:1:2, 60:5:5:5, 70:10:15:2, 75:20:3:5, 75:25:3:5, 80:20:2:3, 85:30:2:5, 90:30:1:1, 95:30:3:5, etc. In one embodiment of the present application, the mass ratio of active material, electrolyte, conductive agent and binder can be (75-85): (20-30): (1-3): (1-5), which is more conducive to improving the construction of electron channels and ion channels in the active material layer. In another embodiment of the present application, the mass ratio of the active material, the electrolyte, the conductive agent and the binder can be (60-85):(10-45):(1-10):(1-15).

[0046] In one embodiment of the present application, the porosity of the electrode sheet is less than or equal to 18%. The smaller the porosity of the electrode sheet, the more conducive it is to improving the energy density of the electrode sheet. Specifically, the porosity of the electrode sheet may be, but is not limited to, less than or equal to 18%, less than or equal to 15%, less than or equal to 14%, less than or equal to 12%, less than or equal to 12%, or less than or equal to 8%, etc. In one embodiment of the present application, the porosity of the electrode sheet may be less than or equal to 15%. In another embodiment of the present application, the porosity of the electrode sheet may be less than or equal to 12%.

[0047] The present application also provides a method for preparing an electrode sheet, which can prepare the electrode sheet in any of the above embodiments. Figure 1 , is a flow chart of a method for preparing an electrode sheet provided in one embodiment of the present application, comprising:

[0048] S101: mixing an active material and a binder to obtain a mixed slurry, and coating the mixed slurry on a surface of a current collector to obtain a prefabricated electrode sheet;

[0049] S102: soaking the prefabricated electrode sheet in a solid filler solution, and drying to obtain the electrode sheet after soaking; the solid filler in the solid filler solution includes an aryl lithium material.

[0050] The electrode sheet preparation method provided in the present application is simple and does not require the application of external pressure. It can obtain an electrode sheet with low porosity and good electronic conductivity and ionic conductivity, which is beneficial to improving the electrochemical performance of solid-state batteries.

[0051] In one embodiment of the present application, in the mixed slurry, the mass ratio of the active material to the binder is (60-99.9): (0.1-20). Specifically, the mass ratio of the active material to the binder may be, but is not limited to, 60:1, 60:10, 60:15, 70:5, 75:10, 80:5, 90:3, 99.9:20, etc. In one embodiment of the present application, the mass ratio of the active material to the binder may be (75-85): (1-2.5). In another embodiment of the present application, the mass ratio of the active material to the binder may be (65-85): (2-5). In yet another embodiment of the present application, the mass ratio of the active material to the binder may be (90-99.9): (0.1-10).

[0052] In one embodiment of the present application, the mixed slurry also includes a conductive agent, which can improve the conductivity of the active material layer. The mass ratio of the active material, the conductive agent and the binder is (60-99.9): (1-20): (0.1-20). Specifically, the mass ratio of the active material, the conductive agent and the binder can be, but is not limited to, 60:1:0.1, 60:1:1, 70:1:3, 75:5:4, 80:5:6, 60:4:7, 80:10:1, 90:15:10, 90:3:5, etc. In one embodiment of the present application, the mass ratio of the active material, the conductive agent and the binder can be (75-85): (1-3): (1-5). In another embodiment of the present application, the mass ratio of the active material, the conductive agent and the binder can be (60-95): (1-10): (1-10).

[0053] In one embodiment of the present application, the mixed slurry also includes an electrolyte, which can improve the ion conductivity between the active material layer and the solid electrolyte layer. The mass ratio of the active material, the electrolyte, the conductive agent and the binder is (60-99.9): (5-50): (1-20): (0.1-20). Specifically, the mass ratio of the active material, the electrolyte, the conductive agent and the binder can be, but is not limited to, 60:5:1:0.1, 60:5:1:2, 60:5:5:5, 70:10:15:2, 75:20:3:5, 75:25:3:5, 80:20:2:3, 85:30:2:5, 90:30:1:1, 95:30:3:5, etc. In one embodiment of the present application, the mass ratio of active material, electrolyte, conductive agent and binder can be (75-85): (20-30): (1-3): (1-5), which is more conducive to improving the construction of electron channels and ion channels in the active material layer. In another embodiment of the present application, the mass ratio of active material, electrolyte, conductive agent and binder can be (60-85): (10-45): (1-10): (1-15).

[0054] In one embodiment of the present application, the shape of the current collector can be designed according to actual needs, and the present application does not make special restrictions. For example, the width of the current collector can be 40mm-50mm, and the thickness can be 6μm-20μm. In one embodiment of the present application, the width of the current collector can be 40mm-45mm, and the thickness can be 6μm-8μm. In another embodiment of the present application, the width of the current collector can be 42mm-50mm, and the thickness can be 10μm-20μm.

[0055] In one embodiment of the present application, the concentration of the solid filler solution is 0.8mol / L-1.2mol / L, which is conducive to uniform filling of the electrode sheet. The solid filler solution can be, but is not limited to, a naphthalene lithium solution, a biphenyl lithium solution, an anthracene lithium solution, an anthracene lithium derivative solution, etc. Specifically, the concentration of the solid filler solution can be, but is not limited to, 0.8mol / L, 0.9mol / L, 1mol / L, 1.1mol / L or 1.2mol / L, etc.; the solvent of the solid filler solution can be, but is not limited to, one or more of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, acetonitrile, N,N-dimethylformamide, and dimethyl sulfoxide. In one embodiment of the present application, the solid filler solution can be a naphthalene lithium solution, with a concentration of 1.0 mol / L, and its preparation method is: naphthalene is mixed with ethylene glycol dimethyl ether, the molar ratio of naphthalene to ethylene glycol dimethyl ether is 1:10, and then the lithium sheet is dissolved in the mixed solution of naphthalene and ethylene glycol dimethyl ether, the molar ratio of naphthalene to lithium sheet is 1:1, and the naphthalene lithium solution is obtained after stirring at room temperature for 40 minutes. This preparation method can be used for the preparation of other solid filler solutions. In another embodiment of the present application, the solid filler solution can be a biphenyl lithium solution, with a concentration of 1.0 mol / L.

[0056] In one embodiment of the present application, the soaking time is 5min-20min. The appropriate soaking time can allow the solid filler to fully fill the pores of the electrode sheet, while preventing the solid filler from reacting with the electrode active material, which is beneficial to reducing the porosity of the electrode sheet. Specifically, the soaking time can be, but is not limited to, 5min, 7min, 9min, 12min, 15min, 17min, 19min, 20min, etc. In one embodiment of the present application, the soaking time can be 5min-10min. In another embodiment of the present application, the soaking time can be 7min-20min.

[0057] In one embodiment of the present application, after the solid filler solution is soaked, the electrode sheet is dried by vacuum drying at room temperature for 10-20 minutes, and the excess solvent in the active material layer of the electrode sheet is removed as much as possible to keep the electrode sheet dry. Specifically, the drying time may be, but is not limited to, 10 minutes, 12 minutes, 13 minutes, 15 minutes, 16 minutes, 18 minutes, 19 minutes, 20 minutes, etc. In one embodiment of the present application, the drying time of the electrode sheet may be 10 minutes to 15 minutes. In another embodiment of the present application, the drying time of the electrode sheet may be 12 minutes to 20 minutes.

[0058] In one embodiment of the present application, the preparation process of the electrode sheet is carried out in an inert atmosphere to prevent the components in the active material layer of the electrode sheet from being contaminated. Specifically, the inert atmosphere may be, but is not limited to, one or more of helium, nitrogen, argon, and neon. In one embodiment of the present application, the inert atmosphere may be helium. In another embodiment of the present application, the inert gas may be argon.

[0059] This application also provides a solid-state battery, see Figure 2 , is a cross-sectional schematic diagram of a solid-state battery provided in one embodiment of the present application. The solid-state battery 100 includes a positive electrode sheet 11 and a negative electrode sheet 12 and a solid electrolyte layer 13 disposed between the electrode sheets. The positive electrode sheet 11 includes a positive electrode collector 111 and a positive electrode active material layer 112 disposed on the surface of the positive electrode collector. The negative electrode sheet 12 includes a negative electrode collector 122 and a negative electrode active material layer 121 disposed on the surface of the negative electrode collector 122. The positive electrode sheet 11 and / or the negative electrode sheet 12 are electrode sheets prepared in any of the above embodiments. The solid electrolyte layer can improve the safety of the solid-state battery. The solid electrolyte layer includes a solid electrolyte and a binder. The binder is one of the binders described in any of the above embodiments. The solid electrolyte includes at least one of an organic polymer, an oxide, and a sulfide. The organic polymer may be, but is not limited to, one or more of polyethylene oxide, polyoxypropylene, polyvinylidene chloride, and polyvinylidene fluoride; the oxide may be, but is not limited to, one or more of lithium steel titanium oxide, lithium steel zirconium oxide, and fast ion conductor; the sulfide may be, but is not limited to, one or more of lithium-containing sulfide, aluminum-containing sulfide, phosphorus-containing sulfide, silicon-containing sulfide, and tin-containing sulfide. In one embodiment of the present application, the solid electrolyte may be a lithium-containing sulfide. In another embodiment of the present application, the solid electrolyte may be polyoxypropylene.

[0060] In one embodiment of the present application, the mass ratio of the solid electrolyte to the binder is (90-99.9): (0.1-10). Specifically, the mass ratio of the solid electrolyte to the binder may be, but is not limited to, 90:0.1, 92:1, 95:2, 96:5, 98:6, 99:6.5, 99.9:10, etc. In one embodiment of the present application, the mass ratio of the solid electrolyte to the binder may be (90-95): (0.1-3). In another embodiment of the present application, the mass ratio of the solid electrolyte to the binder may be (92-99.9): (2-10).

[0061] In one embodiment of the present application, the solid electrolyte layer is prepared by dissolving a solid electrolyte and a binder in a solvent to obtain an electrolyte mixture slurry, and the electrolyte mixture slurry is applied to an electrode sheet or directly forms a solid electrolyte layer. In other words, the electrolyte mixture slurry can be applied to the positive electrode sheet, and after drying, an electrode sheet integrating a solid electrolyte layer and a positive electrode sheet is obtained, which is then assembled with a negative electrode sheet to obtain a solid-state battery; similarly, the electrolyte mixture slurry can also be applied to the negative electrode sheet, and after drying, an electrode sheet integrating a solid electrolyte layer and a negative electrode sheet is obtained, which is then assembled with a positive electrode sheet to obtain a solid-state battery; in addition, the electrolyte mixture slurry can also be formed into a solid electrolyte layer, and then assembled with a positive electrode sheet and a negative electrode sheet to obtain a solid-state battery. The present application does not limit the choice of solvent.

[0062] In one embodiment of the present application, the thickness ratio of the positive electrode active material layer, the negative electrode active material layer and the solid electrolyte layer is (20-50): (10-30): (20-40). Specifically, the thickness ratio of the positive electrode active material layer, the negative electrode active material layer and the solid electrolyte layer can be, but is not limited to, 20:10:20, 25:15:25, 20:18:28, 30:20:25, 35:25:30, 40:28:35, 50:30:37, 50:30:40, etc. In one embodiment of the present application, the thickness ratio of the positive electrode active material layer, the negative electrode active material layer and the solid electrolyte layer can be (35-45): (20-30): (30-40), which is conducive to the effective transmission of charge and improves the theoretical capacity of the solid-state battery. In another embodiment of the present application, the thickness ratio of the positive electrode active material layer, the negative electrode active material layer and the solid electrolyte layer can be (25-50): (15-30): (25-40).

[0063] In one embodiment of the present application, the positive electrode sheet, the negative electrode sheet and the solid electrolyte layer are subjected to rolling treatment to obtain a solid-state battery, the pressure of the rolling treatment is 0.1MPa-20MPa, and the speed of the rolling treatment is 0.1rpm-20rpm. Specifically, the pressure of the rolling treatment may be, but is not limited to, 0.1MPa, 1MPa, 2MPa, 3MPa, 4MPa, 5MPa, 8MPa, 9MPa, 12MPa, 15MPa, 16MPa, 18MPa, 20MPa, etc., and the speed of the rolling treatment may be, but is not limited to, 0.1rpm, 1rpm, 2rpm, 4rpm, 6rpm, 8rpm, 10rpm, 12rpm, 16rpm, 18rpm, 20rpm, etc. In one embodiment of the present application, the pressure of the rolling treatment may be 0.1MPa-10MPa, and the speed of the rolling treatment may be 0.1rpm-10rpm. In another embodiment of the present application, the pressure of the rolling treatment may be 5 MPa-20 MPa, and the rotation speed of the rolling treatment may be 7.5 rpm-20 rpm.

[0064] The present application also provides an electrical device, which includes a solid-state battery in any of the above embodiments, which is beneficial to improving the comprehensive performance of the electrical device. Electrical devices include mobile phones, tablets, watches, VR glasses, cars, etc. In one embodiment of the present application, the solid-state battery can be used in a car to improve the safety of automobile electricity use. In another embodiment of the present application, the solid-state battery can also be used in a mobile phone, which can increase the battery capacity of the mobile phone and improve the battery life.

[0065] The effect of the technical solution of the present application is further illustrated below through specific examples.

[0066] Example 1

[0067] (1) Preparation of positive electrode sheet

[0068] The positive electrode active material (single crystal lithium nickel cobalt manganese oxide particles, particle size 3.85μm), sulfur-based solid electrolyte (Li6PS5Cl, particle size 1μm), conductive agent (carbon) and binder (polyvinylidene fluoride) are mixed to obtain a positive electrode slurry, wherein the mass ratio of positive electrode active material, electrolyte, conductive agent and binder is 70:26:1:3. The positive electrode slurry is coated on aluminum foil, dried at 100°C for 12h, rolled and cut to obtain a prefabricated positive electrode sheet with a diameter of 15mm, wherein the rolling pressure is 0.5MPa and the rolling speed is 1rpm.

[0069] The prefabricated positive electrode sheet was immersed in a solid filler solution (lithium naphthalene solution, solution concentration was 1.0 mol / L) for 12 minutes. After the immersion was completed, the positive electrode sheet was dried to obtain the positive electrode sheet.

[0070] (2) Preparation of negative electrode sheet

[0071] 500 g of negative electrode active material (graphite), 30 g of binder (sodium carboxymethyl cellulose and styrene-butadiene latex in a mass ratio of 2:1) and 1000 mL of deionized water were mixed to obtain a negative electrode slurry; the negative electrode slurry was evenly coated on the negative electrode collector (copper foil), and then dried at 100°C for 12 h, rolled and cut to obtain a 50 mm × 200 mm negative electrode sheet, wherein the rolling pressure was 0.5 MPa and the rolling speed was 1 rpm.

[0072] (3) Preparation of solid electrolyte layer

[0073] 500 g of electrolyte (Li 10 GeP2S 12), 20g of a binder (polyvinylidene fluoride) and 1000mL of toluene are mixed to obtain an electrolyte slurry; the electrolyte slurry is evenly coated on the above-mentioned negative electrode plate, and then dried at 100°C for 12h, rolled and cut to obtain a solid electrolyte layer and a negative electrode plate integrated disc with a diameter of 15mm, wherein the rolling pressure is 0.5MPa and the rolling speed is 1rpm.

[0074] (4) Solid-state battery assembly

[0075] The positive electrode sheet and the solid electrolyte layer and the negative electrode sheet integrated disc prepared above are aligned and rolled, and then packaged in a button battery shell to obtain a solid-state battery. The rolling pressure is 3 MPa and the rolling speed is 1 rpm.

[0076] Example 2

[0077] The difference from Example 1 is that the solid filler solution is a lithium biphenyl solution.

[0078] Example 3

[0079] The difference from Example 1 is that the solid filler solution is an anthracene lithium solution.

[0080] Example 4

[0081] The difference from Example 1 is that the soaking time is 5 minutes.

[0082] Example 5

[0083] The difference from Example 1 is that the soaking time is 15 minutes.

[0084] Example 6

[0085] The difference from Example 1 is that the soaking time is 25 minutes.

[0086] Example 7

[0087] The difference from Example 1 is that the particle size of the positive electrode active material is 6.8 μm.

[0088] Comparative Example 1

[0089] The difference from Example 1 is that the positive electrode plate is not filled with a solid filler.

[0090] Performance Testing

[0091] Positive electrode sheets were prepared from the above-mentioned Examples 1-7 and Comparative Example 1, and the porosity was tested according to GB / T21650.1. The results are shown in Table 1.

[0092] Positive electrode sheets were prepared from the above-mentioned Examples 1-7 and Comparative Example 1, and the mass percentage of the solid filler in the positive electrode sheets was tested. The results are shown in Table 1.

[0093] Solid-state batteries were prepared from the above-mentioned Examples 1-7 and Comparative Example 1, and the charge-discharge cycle test was carried out. The test equipment was LAND CT 2001C, and the test conditions were as follows: the above-mentioned battery was allowed to stand at room temperature (25°C) for 10 minutes; charged at a constant current of 0.1C until 4.3V and then stopped; allowed to stand for 10 minutes; discharged at a constant current of 0.1C until 3V, which was one cycle. Repeat this step, record the discharge capacity, and when the number of cycles reaches 100, the cycle is terminated and the capacity maintenance rate is calculated. Among them, the capacity maintenance rate after 100 cycles = (discharge capacity after 100 cycles ÷ first discharge capacity) × 100%, and the average test results are shown in Table 1.

[0094] Table 1 Performance test results

[0095]

[0096] It can be seen from Examples 1-7 and Comparative Example 1 that the porosity of the positive electrode sheet after being filled with a solid filler is less than that of the positive electrode sheet not filled with a solid filler, and the solid-state battery prepared has a higher specific capacity and better cycle performance. It can be seen from Examples 1 and 4-6 that a suitable soaking time is conducive to obtaining a positive electrode sheet with a lower porosity. This is because a suitable soaking time can ultimately obtain a higher solid filler filling amount, avoiding the problem of insufficient original filling amount of the solid filler, and the problem of a reduction in the final filling amount due to reaction with the electrode active material after reaching the original filling amount, so that a suitable soaking time is conducive to improving the density and energy density of the positive electrode sheet. It can also be seen from Examples 1 and 7 that a suitable combination of the particle size of the positive active material and the electrolyte is conducive to improving the specific capacity and cycle performance of the solid-state battery.

[0097] The above is a preferred embodiment of the present application, but it should not be understood as limiting the scope of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. An electrode sheet, characterized in that: The electrode sheet includes a current collector and an active material layer disposed on the surface of the current collector. The active material layer includes an active material, a binder and a solid filler. The solid filler includes an aryl lithium material.

2. The electrode sheet according to claim 1, characterized in that: The porosity of the electrode sheet is less than or equal to 18%.

3. The electrode sheet according to claim 1, characterized in that: The mass percentage of the solid filler in the electrode sheet is 0.1%-1%.

4. The electrode sheet according to claim 1, characterized in that: The aryl lithium material includes at least one of naphthalene lithium, biphenyl lithium, anthracene lithium and derivatives thereof, and the Young's modulus of the aryl lithium material is 18 GPa-30 GPa.

5. The electrode sheet according to claim 1, characterized in that: The particle size of the active material is 0.5μm-15μm; the active material includes a positive electrode active material or a negative electrode active material; the positive electrode active material includes at least one of lithium cobalt oxide material, lithium manganese oxide material, nickel cobalt manganese material and nickel cobalt aluminum material; the negative electrode active material includes at least one of graphite, acetylene black, graphene, activated carbon, metallic lithium, lithium-indium alloy, silicon and lithium titanate.

6. The electrode sheet according to claim 1, characterized in that: The active material layer further includes a conductive agent, and the mass ratio of the active material, the conductive agent and the binder is (60-99.9):(1-20):(0.1-20).

7. The electrode sheet according to claim 6, characterized in that: The conductive agent includes at least one of graphite, carbon black, acetylene black and graphene; the binder includes at least one of polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, polystyrene, polybutadiene, acrylic resin, epoxy resin, polyethylene oxide, sodium carboxymethyl cellulose and styrene-butadiene latex.

8. The electrode sheet according to claim 1, characterized in that: The active material layer also includes an electrolyte, which includes one or more of an LSPO-type solid electrolyte, a lithium-rich anti-perovskite-type solid electrolyte, a halogen-based solid electrolyte, and a sulfur-based solid electrolyte.

9. The electrode sheet according to claim 8, characterized in that: The particle size of the electrolyte is 1 μm-5 μm, and the mass ratio of the active material to the electrolyte is (60-99.9):(5-50).

10. A method for preparing an electrode sheet, characterized in that: include: The active material and the binder are mixed to obtain a mixed slurry, and the mixed slurry is coated on the surface of the current collector to obtain a prefabricated electrode sheet; The prefabricated electrode sheet is immersed in a solid filler solution, and after the immersion is completed, the electrode sheet is dried to obtain the electrode sheet; the solid filler in the solid filler solution includes an aryl lithium material.

11. The preparation method according to claim 10, characterized in that: The concentration of the solid filler solution is 0.8 mol / L-1.2 mol / L; the soaking time is 5 min-20 min.

12. A solid-state battery, characterized in that: The solid-state battery includes a positive electrode sheet and a negative electrode sheet, and a solid electrolyte layer arranged between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet and / or the negative electrode sheet include the electrode sheet described in any one of claims 1-9 or the electrode sheet prepared by the preparation method described in any one of claims 10-11.

13. The solid-state battery according to claim 12, characterized in that: The positive electrode plate includes a positive electrode collector and a positive electrode active material layer arranged on the surface of the positive electrode collector, and the negative electrode plate includes a negative electrode collector and a negative electrode active material layer arranged on the surface of the negative electrode collector; the thickness ratio of the positive electrode active material layer, the negative electrode active material layer and the solid electrolyte layer is (20-50):(10-30):(20-40).

14. An electrical device, characterized in that: The electrical equipment comprises the solid-state battery according to any one of claims 12-13.